2018
DOI: 10.1016/j.ajhg.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Genome-First Care: Returning Secondary Genomic Findings to Participants and Their Healthcare Providers in a Large Research Cohort

Abstract: There is growing interest in communicating clinically relevant DNA sequence findings to research participants who join projects with a primary research goal other than the clinical return of such results. Since Geisinger's MyCode Community Health Initiative (MyCode) was launched in 2007, more than 200,000 participants have been broadly consented for discovery research. In 2013 the MyCode consent was amended to include a secondary analysis of research genomic sequences that allows for delivery of clinical resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 22 publications
3
106
2
Order By: Relevance
“…The study population was identified from the Geisinger MyCode®Community Health Initiative (MyCode) where adult volunteers from an integrated healthcare delivery system in central Pennsylvania underwent exome sequencing using research protocols detailed in previous publications [1,[18][19][20]. The study cohort was based on a population of 50,726 MyCode participants whose exome sequences were complete, were analyzed to identify potential P/LP variants, and had clinical confirmation of the research result with a report to the EHR to disclose the results between 01/01/2014 and 03/01/2016 [20].…”
Section: Study Populationmentioning
confidence: 99%
“…The study population was identified from the Geisinger MyCode®Community Health Initiative (MyCode) where adult volunteers from an integrated healthcare delivery system in central Pennsylvania underwent exome sequencing using research protocols detailed in previous publications [1,[18][19][20]. The study cohort was based on a population of 50,726 MyCode participants whose exome sequences were complete, were analyzed to identify potential P/LP variants, and had clinical confirmation of the research result with a report to the EHR to disclose the results between 01/01/2014 and 03/01/2016 [20].…”
Section: Study Populationmentioning
confidence: 99%
“…All participants underwent a verbal review of the IRB-approved consent (Western IRB). Study results were returned to participants (within [10][11][12] weeks after the visit), who were encouraged to involve their primary care physicians. Additional details of this study can be found in Perkins et al, 2018 20 .…”
Section: Methodsmentioning
confidence: 99%
“…DiscovEHR findings also showed that ~65% of individuals who carry a pathogenic variant had associated phenotypes observed in their medical records 8 . The initial insights into the delivery of genomic knowledge and approaches for clinical decision and clinical care also have been discussed 9,10,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Several screening programs are initiating genomic sequencing for healthy or unselected populations, irrespective of health status or family history. [3][4][5][6][7][8][9] Amongst these population screening programs there is consensus to return genomic results which are medically significant however there is less concordance regarding which genes fall into this category.…”
Section: Introductionmentioning
confidence: 99%
“…Some cohort studies collect a three-four generation pedigree at recruitment, 3,10 while others gather family history once a clinically significant genomic variant is detected. 6,8,9 There is emerging evidence that in unselected populations, 48%-60% of individuals identified as having a clinically actionable variant have no associated family history. 8,9,11 A case control study observed a similar prevalence of Ashkenazi Jewish BRCA founder variants amongst individuals with and without breast cancer in their family 12 , and a more recent study found the frequency of clinically actionable variants was similar amongst breast cancer patients who met and did not meet clinical criteria for genetic testing.…”
Section: Introductionmentioning
confidence: 99%